RANCANG BANGUN GENERATOR TURBIN ANGIN PUTARAN RENDAH SEBAGAI PEMBANGKIT ENERGI LISTRIK ALTERNATIF DI DAERAH PESISIR - rochman, sagita; Sembodo, Budi Prijo (WAHANA, 2018)
Axial Flux Permanent Magnet Generator (AFPMG) of wind turbine generator has been successfully designed and fabricated. The generator has been designed for wind speed in the range of 2-6 m/s and low rotation. The main purpose of study was to design and analyze wind turbine generator with the low speed of wind that can be generated electric power for household. The results showed that the prototype of wind turbine can be generated voltage around 22.5 - 157.1 V with the rotation of the rotor shaft at 150 - 1000 rpm. Meanwhile, the prototype can be generated output power of 98.5 Watt shaft rotation of 1000 rpm when its connected to load. Both current and voltage can be achieved around 151.4 V and 0.651 A, respectively.The prototype was then conneted with DC to DC converter and DC to AC converter to generate output power of 500 W.